2018
DOI: 10.1177/1071100718773998
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Randomized Trial of Electrolysis for Chronic Plantar Heel Pain

Abstract: Level I, randomized controlled trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(48 citation statements)
references
References 38 publications
(74 reference statements)
0
47
0
1
Order By: Relevance
“…One of the most innovative techniques today for the treatment of tendinopathies is percutaneous electrolysis due to its powerful effect in reducing pain and increasing functionality, especially in load tendons in the lower limb [15]. There is only a modest scientific evidence demonstrating the effects of electrolysis in reducing pain and increasing function in both lower and upper extremity tendon structures, which is drawing the attention of physicians and physical therapists in both clinical and scientific arenas [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most innovative techniques today for the treatment of tendinopathies is percutaneous electrolysis due to its powerful effect in reducing pain and increasing functionality, especially in load tendons in the lower limb [15]. There is only a modest scientific evidence demonstrating the effects of electrolysis in reducing pain and increasing function in both lower and upper extremity tendon structures, which is drawing the attention of physicians and physical therapists in both clinical and scientific arenas [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…PHP was caused by varieties of physiological factors [7][8][9]; the most common pathological factor in the population was PF [10,11]. Research studies on the PF and treatments of PF had a long tradition [2,13,15,30]. Histological studies had found that PF had a fascia fragmentation and degeneration [9], which may be caused by PCS at the plantar bottom [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Plantar heel pain (PHP) is a common disease with a high incidence in different races [1][2][3]. It was expected to cost more than 200 million of dollars in PHP treatment [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The needle was ultrasound-guided inserted into the common tendon of the lateral epicondyle and left in situ for 90 s without galvanic current. This needling procedure has been previously used in a randomized clinical trial investigating the effects of percutaneous electrolysis in people with plantar heel pain [ 28 ].…”
Section: Methodsmentioning
confidence: 99%